Web Application for Pollution-Aware Route Planning - Asfari, Joud (Wellington Faculty of Engineering Symposium, 2023)
Air pollution is linked to adverse effects on respiratory and cardiovascular health. It is estimated that outdoor environmental air pollution was responsible for causing 4.2 million premature deaths worldwide in 2019. Studies indicate that mitigating exposure to air pollution can lower mortality rates associated with it. One way to reduce exposure is by planning better travel routes for individuals at risk. As it stands, people sensitive to air pollution in Aotearoa New Zealand and in many countries internationally do not have access to tools that would assist in decreasing their outdoor exposure to it. Additionally, route-planning tools are limited in how the search is done and what metrics are used. To address this, a web application for route planning using air pollution data has been developed. The web application has three main components; a database server, a service logic server that contains the search algorithm and pre-processing scripts, and a user interface that communicates with the service logic server. Air pollution readings were taken in the Greater Wellington region and are spatiotemporal data mapped onto real geographic locations. Data is normalised using New Zealand’s National Environmental Standards for Air Quality (NES-AQ). The pathfinding algorithm uses a distance and air pollution-based heuristic with weights for all parameters. The resulting application allows users to customise route searches to prioritise or exclude air pollutants and also include road distance as part of the search heuristic. The paths found by the application are consistent and reproducible and allow users the ability to fine-tune searches to fit their needs and gain insights about air pollution in Wellington roads.